Integration of Javanese Cultural Workshops to Enrich Museum Visitor Experiences - Septi Yulisetiani; Eko Prayitno Joko (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2024)
Museums play a strategic role as sources of knowledge, inspiration, and motivation for visitors. Each museum features unique characteristics and artifacts with aesthetic, historical, and cultural value, offering diverse visitor experiences. Visitors can fully appreciate these experiences when they explore the museum's collections. Therefore, museum management must innovate to enhance visitor engagement. This study examines the integration of Javanese culture workshops to improve museum visitor experiences, focusing on a case study of the UNS Museum managed by PUI Javanologi. The museum houses artifacts related to UNS’s history and Javanese cultural research by PUI Javanologi. Data collection involved observation, interviews, and document analysis, with interactive analysis techniques and triangulation ensuring data validity. Results indicate that Javanese culture workshops enhance visitor experiences. Visitors enthusiastically explore Javanese artifacts, read descriptions, and learn fascinating stories from educators. Workshop participants gain richer experiences by learning traditional dances, batik-making, herbal medicine preparation, and children’s games, alongside insights into Javanese cultural research. These workshops increase visitor interest, extend visit duration, and create meaningful, educational experiences. Moreover, they contribute to preserving cultural heritage. Integrating Javanese culture workshops represents a strategic innovation in museum management, strengthening cultural identity and enhancing its appeal.